Volume 1A, Symposia: Turbomachinery Flow Simulation and Optimization; Applications in CFD; Bio-Inspired and Bio-Medical Fluid M 2016
DOI: 10.1115/fedsm2016-7803
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Time Dependent Physio-Chemical Model for Thrombus Formation and Growth

Abstract: In this study, a shear-dependent continuum model for platelet activation, adhesion and aggregation is validated using computational fluid dynamics (CFD). To take the presence of red cells into account, a combination of excess-platelet boundary layer and enhanced mass diffusivity of platelets and large species is used to mimic this behavior. The model has been validated under three different shear conditions and two different heparin levels. Also three-dimensional simulations were carried out to evaluate the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For platelets in PRP, it can be assumed that they diffuse in plasma solely due to their Brownian motion (D b;PLT ). However, in whole blood the diffusion coefficient of platelets can be dramatically augmented (up to three orders of magnitude) due to margination (Hosseinzadegan and Tafti, 2016). This effect, referred to as the shear-enhanced or the shear rate-dependent mass diffusivity of Figure 4.…”
Section: Platelet Marginationmentioning
confidence: 99%
“…For platelets in PRP, it can be assumed that they diffuse in plasma solely due to their Brownian motion (D b;PLT ). However, in whole blood the diffusion coefficient of platelets can be dramatically augmented (up to three orders of magnitude) due to margination (Hosseinzadegan and Tafti, 2016). This effect, referred to as the shear-enhanced or the shear rate-dependent mass diffusivity of Figure 4.…”
Section: Platelet Marginationmentioning
confidence: 99%
“…Hence, this method could be coupled with atomistic-continuum simulations. [33][34][35][36] It was also concluded that the method for estimation of the resistance to defect propagation in nanoscales could be used in traction-separation law in continuum mechanics. V-notches and U-notches are complex defects, which should be accurately evaluated by applying the J-integral method.…”
Section: J-integral and Stress Intensity Factormentioning
confidence: 99%